A comparative analysis of anthropometric indices for diagnosing obstructive sleep apnea among American Adults - Wenjia Liu; Shangyi Song; Hongguo Zhang; Chunping An (Scientific Reports)
Abstract The occurrence of obstructive sleep apnea (OSA) syndrome is related to not only the overall obesity, but also the local distribution of fat. Therefore, we introduced anthropometric indicators to comprehensively assess the risks associated with obesity, including body mass index (BMI), which is used to assess the overall obesity, together with waist circumference (WC), body roundness index (BRI), visceral adiposity index (VAI) and lipid accumulation product (LAP), all of which reflect fat distribution. This cross-sectional study analyzed data from the 2005–2008 and 2015–2018 NHANES cycles, comprising 8966 participants. Logistic regression models were used to examine the associations between anthropometric indices and OSA, adjusting for relevant covariates. Receiver operating characteristic (ROC) curves were constructed, and values of the area under the curve (AUC) were calculated to assess diagnostic performance. AUC comparisons between men and women were conducted using the DeLong’s test. After adjusting for covariates, WC and BMI emerged as the strongest diagnostic indicators of OSA risk. A ROC analysis revealed that WC and BMI had higher diagnostic performance performance among women (AUC: WC: 0.651, BMI: 0.653) than men (AUC: WC: 0.616, BMI: 0.619). Other indices demonstrated weaker diagnostic abilities. Both WC and BMI demonstrated a strong diagnostic ability for OSA across both sexes, with slightly better performance observed among women. These findings suggest that WC and BMI are practical and effective tools for the early detection, risk stratification and management of OSA in clinical practices.